Constructive representation at the plane collineations placing quadric itself - Harah, M. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:М. М. Харах. Конструктивное отображение на плоскость коллинеаций, переводящих квадрику в себяM. Harah. Kolineacijų, pervedančių kvadriką į save, konstruktyvus atvaizdavimas plokštumoje